"Beati Gli Operatori Di Pace ... " (Mt 5, 9): La Virtù Della Pace Nell'esegesi Patristica E Nel Pensiero Teologico Contemporaneo - Artyušin, Ieromonaco Filofey (Lateranum, 2023)
In the present article is explored the theological meaning of the seventh beatitude of the Sermon on the mount: Blessed are the peacemakers (Mt 5,9). On the basis of the chosen patristic commentaries an effort is made to found in them a main spiritual thread which could shed light on the actual challenge of war. The theological analysis parts from several contemporary works of famous theologians. Among them there are members of both Catholic and Orthodox Churches. The results of the research are resumed in the final synthesis made on the basis of an ascetical-spiritual work of the elder (in Russian, starez) Nicon Vorobjov whose thoughts on the Principles of life resound in the present context.